2017
DOI: 10.1007/s00228-017-2274-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospital electronic prescribing system implementation impact on discharge information communication and prescribing errors: a before and after study

Abstract: PurposeThe study aimed to test the hypothesis that hospital electronic prescribing and medicine administration system (HEPMA) implementation impacted patient discharge letter quality, nature and frequency of prescribing errors.MethodA quasi experimental before and after retrospective case note review was conducted in one United Kingdom district general hospital. The total sample size was 318 (random samples of 159 before and after implementation), calculated to achieve a 10% error reduction with a power of 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…We have identified that medication poses a frequent and enduring risk to patient safety following discharge from hospital, which reinforces care transfer being a WHO Global Patient Safety Challenge priority for action. We found across included studies that a median of one in two adult and elderly patients are affected by at least one ME post-hospital discharge, one in two affected by one or more UMD, and one in five affected by one or more ADEs (the median rate of MEs, UMDs and ADEs post-hospital discharge was 53% [IQR 33-60.5] (n = 5), 50% [IQR (n = 11) and 19% [IQR [16][17][18][19][20][21][22][23][24] (n = 7), respectively). We also reported emerging evidence of the nature of these risks, with a median of nearly one third of adult and elderly patients affected by clinically serious ADEs post-hospital discharge and medication classes most commonly reported with ADEs as antibiotics, antidiabetics, analgesics and cardiovascular drugs.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified that medication poses a frequent and enduring risk to patient safety following discharge from hospital, which reinforces care transfer being a WHO Global Patient Safety Challenge priority for action. We found across included studies that a median of one in two adult and elderly patients are affected by at least one ME post-hospital discharge, one in two affected by one or more UMD, and one in five affected by one or more ADEs (the median rate of MEs, UMDs and ADEs post-hospital discharge was 53% [IQR 33-60.5] (n = 5), 50% [IQR (n = 11) and 19% [IQR [16][17][18][19][20][21][22][23][24] (n = 7), respectively). We also reported emerging evidence of the nature of these risks, with a median of nearly one third of adult and elderly patients affected by clinically serious ADEs post-hospital discharge and medication classes most commonly reported with ADEs as antibiotics, antidiabetics, analgesics and cardiovascular drugs.…”
Section: Main Findingsmentioning
confidence: 99%
“…There is an emerging body of literature that reports on the prevalence and nature of MEs and ADEs [16] as well as medication discrepancies [17][18][19] at the point of hospital discharge (i.e. before patients return home).…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies assessed the impact of EMS on PE rates, with a range of denominators reported across studies. 41–43 , 45 , 51 , 53–55 , 57 , 58 Heterogeneity in error rate reporting and study settings prevented meta-analysis of the association between EMS and rates of PE. EMS, with or without CDS, was associated with a significant reduction in PE rate in all but 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies focused on adults [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], ten on a paediatric or neonatal population [57][58][59][60][61][62][63][64][65][66], and five included a mixed population [67][68][69][70][71] (see Table 1). Ten studies were based in the US [37,41,42,48,54,57,58,64,67,70], eight in the UK [39,45,49,50,53,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Selection errors [45,49,60,68] and duplicate errors [38,47,60] were the TGE most frequently identified. Due to the simpler nature of some ePrescribing systems, free-text errors were possible [67].…”
Section: Study Cds Presentmentioning
confidence: 99%